Overexpression of Lin28b in neural stem cells is insufficient for brain tumor formation, but induces pathological lobulation of the developing cerebellum - Wefers, Annika K.; Lindner, Sven; Schulte, Johannes Hubertus; Schüller, Ulrich (The cerebellum, 2017)
LIN28B is a homologue of the RNA-binding protein LIN28A and regulates gene expression during development and carcinogenesis. It is strongly upregulated in a variety of brain tumors, such as medulloblastoma, embryonal tumor with multilayered rosettes (ETMR), atypical teratoid/rhabdoid tumor (AT/RT), or glioblastoma, but the effect of an in vivo overexpression of LIN28B on the developing central nervous system is unknown. We generated transgenic mice that either overexpressed Lin28b in Math1-positive cerebellar granule neuron precursors or in a broad range of Nestin-positive neural precursors. Sections of the cerebellar vermis from adult Math1-Cre::lsl-Lin28b mice had an additional subfissure in lobule IV. Vermes from p0 and p7 Nestin-Cre::lsl-Lin28b mice appeared normal, but we found a pronounced vermal hypersublobulation at p15 and p21 in these mice. Also, the external granule cell layer (EGL) was thicker at p15 than in controls, contained more proliferating cells, and persisted up to p21. Consistently, some Pax6- and NeuN-positive cells were present in the EGL of Nestin-Cre::lsl-Lin28b mice even at p21, and we detected more NeuN-positive granule neuron precursors in the molecular layer (ML) as compared to control. Finally, we found some residual Pax2-positive precursors of inhibitory interneurons in the ML of Nestin-Cre::lsl-Lin28b mice at p21, which have already disappeared in controls. We conclude that while overexpression of LIN28B in Nestin-positive cells does not lead to tumor formation, it results in a protracted development of granule cells and inhibitory interneurons and leads to a hypersublobulation of the cerebellar vermis.